Air entrainment and oxygen transfer in high-head gated conduits - Ozkan, F.; Baylar, A.; Ozturk, M. (Thomas Telford Publishing, 2006)
Air may be entrained into flowing water by design or inadvertently. Air entrained into flowing water at a hydraulic structure may be beneficial from the standpoint of oxygen recharge. When the gate of a high-head outlet conduit is partly opened, a negative pressure draws the air in through the air vent. Air that is entrained into the water is instantly forced downstream in the form of small air bubbles. The solution of oxygen into the water results from the air entrainment downstream of the high-head gated conduit. Moreover, high pressure in high-head gated conduit flow systems also facilitates the solution of oxygen into the water. Numerous model studies and a few field measurements have been conducted to determine the amount of air demand by closed conduits. The literature search did not identify any published analytical or physical studies of the dissolved oxygen levels produced in gated conduits. Therefore, experimental studies were conducted to investigate aeration efficiency of high-head gated conduit flow systems by using a simplified experimental configuration. It was observed from the results that almost full oxygen transfer, up to the saturation value, occurred at high-head gated conduits. Accordingly, it was concluded that high-head gated conduit flow systems have an extremely high efficiency for transferring oxygen from air bubbles to water.
Keywords: environment; hydraulics & hydrodynamics